Reconstruction of Community Knowledge in the Process of Making Potato Dodol Kerinci on the Criteria of Product Halalness Using Ethnoscience Approach - Indah Kencanawati; Lia Angela (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
This study aims to reconstruct the community's original knowledge in the process of making potato dodol into scientific knowledge according to the halal criteria of a product determined by the halal product guarantee system. The research method used is descriptive qualitative based on ethnoscience with the scope of examination including document analysis, interviews and documentation. Data collection is done directly to respondents (business actors) by purposive sampling. The data obtained were analyzed according to the criteria for the halal product assurance system which includes: commitment and responsibility, materials, halal product processes, products and monitoring and evaluation. Data analysis is carried out with traceability according to the halal document of a product. The results showed that the process of making potato dodol according to community knowledge  can be transformed into scientific knowledge was acquired and developed from generation to generation. The stage of start from preparing ingredients, boiling, milling, mixing the dought with other ingredients, kneading, printing and cutting, drying, packaging and labeling. It can be concluded that the procedure for making potato dodol  developed through generations is comply with Islamic law, star from use of tools, production facilities, packaging systems, storage, distribution that are free of non-halal materials which meet standards and can be consumed by the public.